Village Transformation Through the Healthy and Prosperous Village Program: Implementation in Suka Damai Village, North Tambusai District - Ummul Fithriyyah, Mustiqowati; Apriani, Siska; Monalisa, Monalisa (Iapa Proceedings Conference, 2024)
So far, villages have often been neglected due to the tendency of development in urban areas. This study aims to realize the implementation of the Sustainable Development Goals of the Village through a healthy and prosperous village program in Suka Damai Village, North Tambusai District. The research method uses qualitative data collection techniques of observation, interviews and documentation. Based on the results of the study, it can be concluded that the implementation of the Sustainable Development Goals of the Village in healthy and prosperous villages has achieved indicators, namely births in health service facilities and using skilled health workers reaching 100%, maternal mortality rates reaching 0%, infant mortality rates reaching 0%, basic infant immunization reaching 100%, deaths and serious injuries due to traffic accidents reaching 0% and access to proper sanitation reaching 100%. While the indicators that have not been achieved are BPJS Kesehatan which has not reached 100% of the population, the percentage of smokers ≤18 years has not reached 0%, the prevalence of contraceptive use in married residents aged 18-49 years has not reached 100%, the birth rate in adolescents aged 15-19 years has not reached 0% and access to clean drinking water has not reached 100%. The achievement of the Village SDGs indicators in this case is driven by good cooperation and coordination between village governments.